2013
DOI: 10.1017/s0025315413001379
|View full text |Cite
|
Sign up to set email alerts
|

Spatial segregation and similar trophic-level diet among eastern Canadian Arctic/north-west Atlantic killer whales inferred from bulk and compound specific isotopic analysis

Abstract: Killer whales in the Eastern Canadian Arctic (ECA) prey on narwhal, beluga, bowhead whales and seals, while further south in the north-west Atlantic (NWA), killer whales off the coast of Newfoundland and Labrador prey on both marine mammals and fish. Bulk and amino acid (AA) specific isotopic composition of dentinal collagen in teeth of 13 ECA/NWA killer whales were analysed to assess the degree, if any, of dietary specialization of killer whales across the region. Dentine was sampled from within annual growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 78 publications
(148 reference statements)
6
55
1
Order By: Relevance
“…However, even the multi‐TDF Glu‐ Phe approach still appeared to underestimate wild penguin TP CSIA values. Several recent studies on marine mammals similarly found that while a multi‐TDF equation improved estimates of TP CSIA , the calculated TP CSIA values were still ecologically unrealistic (Matthews and Ferguson , Ruiz‐Cooley et al. ).…”
Section: Incorporating Tdf Variability Into Trophic Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, even the multi‐TDF Glu‐ Phe approach still appeared to underestimate wild penguin TP CSIA values. Several recent studies on marine mammals similarly found that while a multi‐TDF equation improved estimates of TP CSIA , the calculated TP CSIA values were still ecologically unrealistic (Matthews and Ferguson , Ruiz‐Cooley et al. ).…”
Section: Incorporating Tdf Variability Into Trophic Ecologymentioning
confidence: 99%
“…In recent years, the basic assumption of a constant TDF Glu-Phe value has come under increasing scrutiny. A number of field studies calculating TP CSIA in upper trophic-level consumers (including cephalopods, teleost fishes, elasmobranchs, marine mammals, and penguins) have noted that assuming a constant TDF Glu-Phe value of 7.6‰ often led to substantially underestimated TP CSIA relative to expected values from a whole host of other metrics, including gut content analysis and feeding observations (Lorrain et al 2009, Dale et al 2011, Choy et al 2012, ruiz-Cooley et al 2013, Matthews and Ferguson 2014. Bradley et al (2015) used an elegant linear regression approach to back-calculate a TDF Glu-Phe value of 5.7‰ ± 0.3‰ from 224 wild-caught teleost fishes (47 species) based on the difference in consumer δ 15 N Glu and δ 15 N Phe values and predicted TP from published stomach content analyses.…”
Section: Trouble In Paradise: Questioning the "Universality" Of 76‰mentioning
confidence: 99%
“…Ecological interpretations of tissue δ 13 C and δ 15 N values can be complicated by the confounding influences of trophic and physiological factors, as well as baseline variation on multiple spatial and temporal scales (see Matthews and Ferguson ). In contrast, the oxygen isotope composition of freshwater and marine vertebrate tissues primarily reflects that of ambient water (Yoshida and Miyazaki ; Coulson et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Riofrío‐Lazo et al. ; Matthews and Ferguson ). To assess the applicability of δ 18 O analysis of dentine hydroxyapatite (Ca 10 [PO 4 ,CO 3 ] 6 [OH,CO 3 ] 2 ) in this context, we measured δ 18 O values of structural carbonate and phosphate ( δ 18 O SC and δ 18 O P ) in dentine of odontocete species from marine water bodies ranging in surface water δ 18 O values (LeGrande and Schmidt ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation